PENGARUH BEBERAPA JENIS PAKAN TANAMAN KEHUTANAN TERHADAP KUALITAS DAN KUANTITAS KOKON ULAT SUTERA EMAS (Cricula trifenestrata Helf) - Hartono .; Terry M. Frans; Josephus I. Kalangi (Universitas Sam Ratulangi, 2016)
ABSTRACTTHE INFLUENCE OF SOME KIND OF FORESTRY FEED PLANTS TO THEQUALITY AND QUANTITY OF Cricula trifenestrata Helf COCOONSThe research aims to look at the influence of some types on liking of forestry plantsfeed (preference), life cycle, and the quantity and quality of gold silkworm cocoons C.Trifenestrata. This research was conducted from July to October 2015. Data collection wasperformed by the method of completely randomized design (CRD). Data collection wasperformed by completely randomized design (CRD) method.Specifically to see the effect on the quantity of cocoon, research using the completelyrandomized design (CRD) method. Observation is done by counting the number of larvae oneach type of feed. Data were analyzed to find the value of the average percentage for eachtype of feed.The results showed that avocado feed into the main host of C. trifenestrata forpreferred and easy to digest, and provide the best effect against the liking (preference) that is: 24.5%, while eating cinnamon lower than the avocado feed 22.2%, compared to eatingavocado and cinnamon Nantu feed have a lower preference level that is 19.2%, a lower levelcompared to eating avocado, cinnamon, Nantu feed, indicated by the cempaka feed that is17.7%, while feed with the lowest preference level is mahogany feed with 16.7%. TheAverage of long life cycle of insects that are kept on each type of feed as the host,respectively : Cempaka (61,7 days), Mahogany ( 55,9 days), Nantu (49,3 days), Avocado(72,3 days), dan Cinnamon (64,7 days). Avocado feed give the best effect on the quantity ofcocoons prodeced, that is: cocoons weight (95,56 g), heavy leather cocoons (13,9 g), andpercentage cocoons leather (27,07 g). Avocado feed give the best effect on the quality ofcocoon formed (shape and cocoons colour)Keyword : Liking research (preference), Cricula trifenestrata Helf, wood.